Drug Hazard Education for Adolescents in Mranggen District, Demak Regency - Ahmad Hadi Prayitno; Masroor Ridwan (LPPM Universitas Islam Sultan Agung, 2026)
The consequences of the abuse of narcotic and psychotropic drugs can be felt physiologically to the point of causing tissue and organ damage. Narcotics are very dangerous to the physical, psychological and social environment. The use of narcotics hinders development and progress and degrades the dignity and quality of a nation. Regulations on narcotics crimes are regulated in Law Number 35 of 2009 concerning Narcotics. The legal sanction for this criminal act is adjusted to the form of the perpetrator's actions. Therefore, it is very necessary to hold education about the dangers of narcotics abuse in rural areas to educate teenagers and students around the village. Regarding sanctions and criminal provisions for users and dealers, they are found in Chapter XV of the provisions of Articles 111 – 129 of the Narcotics Law. One example of a case discussed in community service this time is the case of class I narcotics dealers in the lower class. Sanctions regarding the possession of class I narcotics in the form of plants are regulated in Article 111 of the Narcotics Law, while the possession of class I narcotics not in the form of plants is regulated in Article 112 of the Narcotics Law. For producers or distributors of narcotics in group I, sanctions are regulated in Article 113 of the Narcotics Law. Sanctions regarding the sale or purchase of class I narcotics are regulated in Article 114 of the Narcotics Law.